2021
DOI: 10.1021/acsami.1c17629
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Joint Paint for Efficient Cartilage Repair by Simultaneously Regulating Cartilage Degeneration and Regeneration in Pigs

Abstract: Irregular partial-thickness cartilage defect is a common pathogenesis of osteoarthritis (OA) with no available treatment in clinical practice. Currently, cartilage tissue engineering is only suitable for a limited area of full-thickness cartilage defect. Here, we design a biomimetic joint paint for the intractable partial-thickness cartilage defect repair. The joint paint, composed of a bridging layer of chondroitin sulfate and a surface layer of gelatin methacrylate with hyaluronic acid, can quickly and tight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…Combined with the introduction of photocross-linked HAMA hydrogels and ultrasonically emulsified nHAP, the mechanical properties of the composite hydrogels were significantly reinforced. Besides, the hydrogen proton 1 H NMR spectra of the composite hydrogels demonstrated that the methacrylated gelatin and hyaluronic acid methacrylate successfully photocrosslinked with each other and simultaneously retained –CH CH–CH 3 or –CH CH 2 functional groups, which is consistent with the published literature [ 29 , 33 , 34 ]. The physiological roles of USC EXOs implicated in osteogenesis, angiogenesis, and anti-inflammation have been demonstrated [ 11 , 35 ].…”
Section: Discussionsupporting
confidence: 89%
“…Combined with the introduction of photocross-linked HAMA hydrogels and ultrasonically emulsified nHAP, the mechanical properties of the composite hydrogels were significantly reinforced. Besides, the hydrogen proton 1 H NMR spectra of the composite hydrogels demonstrated that the methacrylated gelatin and hyaluronic acid methacrylate successfully photocrosslinked with each other and simultaneously retained –CH CH–CH 3 or –CH CH 2 functional groups, which is consistent with the published literature [ 29 , 33 , 34 ]. The physiological roles of USC EXOs implicated in osteogenesis, angiogenesis, and anti-inflammation have been demonstrated [ 11 , 35 ].…”
Section: Discussionsupporting
confidence: 89%
“…Surprisingly, the long-term toxicity profile of local distribution ( Saifi et al, 2018 ) as well as the body wide non-targeting infiltration ( Mohammadpour et al, 2019 ; Wu et al, 2019 ) of nanoparticles are still one of the most important concerns when drug-loaded nano-emusions or nanoparticles were intraarticularly injected. On the contrary, hydrogels spheroids at micro-scale were proven to be more available for the direct release of cells, growth factors and drugs ( Annamalai et al, 2019 ; Volpatti et al, 2021 ), and could provide as a dense barrier for inflammatory erosion and chondrocyte apoptosis ( Wei et al, 2021 ; Han et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the university has been committed to the study of photosensitive hydrogels for TE applications. Recently, the research group of Ouyang from Zhejiang Univ developed a biomimetic joint paint containing GelMA with hyaluronic acid which can be rapidly activated by light for the treatment of cartilage defect ( Wei et al, 2021 ). However, as the two countries that published the most papers, the United States and China did not cooperate closely in this field.…”
Section: Discussionmentioning
confidence: 99%